Korean Red Ginseng Improves Blood Pressure Stability in Patients with Intradialytic Hypotension. (8th May 2012) - Chen, I-Ju; Chang, Ming-Yang; Chiao, Sheng-Lin; Chen, Jiun-Liang; Yu, Chun-Chen; Yang, Sien-Hung; Liu, Ju-Mei; Hung, Cheng-Chieh; Yang, Rong-Chi; Chang, Hui-Chi; Hsu, Chung-Hua; Fang, Ji-Tseng
Abstract : Introduction . Intradialytic hypotension (IDH) is a common complication during hemodialysis which may increase mortality risks. Low dose of Korean red ginseng (KRG) has been reported to increase blood pressure. Whether KRG can improve hemodynamic stability during hemodialysis has not been examined. Methods . The 8-week study consisted of two phases: observation phase and active treatment phase. According to prehemodialysis blood pressure (BP), 38 patients with IDH were divided into group A (BP ≥ 140/90 mmHg, n = 18) and group B (BP < 140/90 mmHg, n = 20). Patients were instructed to chew 3.5 gm KRG slices at each hemodialysis session during the 4-week treatment phase. Blood pressure changes, number of sessions disturbed by symptomatic IDH, plasma levels of vasoconstrictors, blood biochemistry, and adverse effects were recorded. Results . KRG significantly reduced the degree of blood pressure drop during hemodialysis (P < 0.05 ) and the frequency of symptomatic IDH (P < 0.05 ). More activation of vasoconstrictors (endothelin-1 and angiotensin II) during hemodialysis was found. The postdialytic levels of endothelin-1 and angiotensin II increased significantly (P < 0.01 ). Conclusion . Chewing KRG renders IDH patients better resistance to acute BP reduction during hemodialysis via activation of vasoconstrictors. Our results suggest that KRG could be an adjuvant treatment for IDH.